The Arsenal of Means Used by a Conductor in Decoding an Opera Score - ICHIM, Traian (Studia Universitatis Babes-Bolyai Musica, 2023)
For a conductor the text of the score is that building material used in the creation of “his own world”. This paper examines the system of means used by a conductor in creating an opera performance. A transformation of the “mobile” and “fixed” elements of the score into a magnificent world of opera performance. The study is based on material from a production of the opera Orpheus by Claudio Monteverdi, directed by Jean-Pierre Ponnelle, conductor being Nikolaus Harnoncourt. This staging can certainly be considered one of the most striking examples of the remarkable interplay between conductor and director in an opera production. Each new revised edition of different opera titles, over the centuries, becomes the product of the personal vision of the creators, acting from the point of view of the aesthetics of its time.